1980
DOI: 10.1080/00150198008226080
|View full text |Cite
|
Sign up to set email alerts
|

Improper ferroelectrics for pyroelectric detection of infrared radiation

Abstract: The a b s e n c e o f d i e l e c t r i c d i v e r g e n c e i n i m p r o p e r f e r r o e l e c t r i c s makes i t p o s s i b l e t o o b t a i n a h i g h p y r o e l e c t r i c f i g u r e of m e r i t n e a r their t r a n s ition t e m p e r a t u r e . R e s u l t s o f m e a s u r e m e n t s c a r r i e d o u t a s a f u n c t i o n o f t e m p e r a t u r e on r e p r e s e n t a t i v e s o f three c l a s s e s o f i m p r o p e r ferroelect r i c s : r a r e -e a r t h m o l y b d a t e s , p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…It is emphasized that the maximum M 2 value of 1 is also obtained near the phase transition temperature, which reaches up to ≈16 × 10 −2 cm 3/2 J −1/2 , being an order of magnitude larger than that of TGS. To assess the experimental figures, we further performed theoretical calculations using a thermodynamic model on the basis of Gibbs free‐energy expression for improper ferroelectrics . As shown in Figure , the fitting traces agree fairly well with experimental results, and display a consistent tendency with the peak value at T c .…”
supporting
confidence: 59%
“…It is emphasized that the maximum M 2 value of 1 is also obtained near the phase transition temperature, which reaches up to ≈16 × 10 −2 cm 3/2 J −1/2 , being an order of magnitude larger than that of TGS. To assess the experimental figures, we further performed theoretical calculations using a thermodynamic model on the basis of Gibbs free‐energy expression for improper ferroelectrics . As shown in Figure , the fitting traces agree fairly well with experimental results, and display a consistent tendency with the peak value at T c .…”
supporting
confidence: 59%
“…A single rotational mode (primary order parameter) was found to induce improper ferroelectricity in perovskite oxides ( 8 ). Similar coupling terms of the Landau type free energy model can be found in improper ferroelectrics including rare-earth molybdates, propionates, and boracites ( 9 ). More recently, improper ferroelectric di- n -butylaminium trifluoroacetate used the same form of the equation ( 10 ).…”
supporting
confidence: 52%
“…However, it is possible to avoid this problem if the spontaneous polarization is induced by only a single rotational mode, making such materials improper rather than hybrid-improper ferroelectrics. Materials of this nature could find use in high-temperature electronic applications such as sensors [23].…”
Section: Introductionmentioning
confidence: 99%
“…such as sensors. 22 Our previous work has shown that although both inphase and out-of-phase rotations are required to lift inversion symmetry in [001]-ordered double perovskites, only out-of-phase rotations, which are described by a single mode, are needed if the A-sites are ordered along the [111] direction (the difference in cation ordering is shown in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%